Yo y tú; la misma alma: sobre la aporía de la intersubjetividad en la fenomenología de Husserl. (2011)
This article aims to address the rising debate about the plane aporia phenomenological constitucion of otherness; by Husserl in the Cartesian Meditations. Because of the length of the text; we must focus on the Fifth Meditacion (In the transcendental sphere of Being is revealed as intersubjectivity monadological); which can be considered as the climax and centerpiece of the exhibition made by Husserl; which attempts to account the relationship between operant subjectivity (ego constituent) and otherness constituted. From the outset; the aporia of intersubjectivity is determined by the inability to interpret the status of otherness without traveling by a preponderance that the ego is operating on another; ie; the inability to accept the objectivity of intersubjectivity if not is presumed certainty of the transcendental subjec.